Factors that influencing quality graduates at a private university / Nor Azira Razalli - Razalli, Nor Azira (Faculty of Business and Management, 2005)
This research is about "Factors That Influence Quality Graduates at a Private University" was been done at University Tenaga Nasional which located at Bangi, Selangor. This university was formed up in 1994, was known as Institut Kejuruteraan Teknologi Tenaga Nasional (IKATAN). Since 1997, it has been conferred a university status. Universiti Tenaga Nasional (henceforth, UNITEN) is subsidiary of Tenaga Nasional Berhad (TNB), one of the largest utility companies in South East-Asia. It is one of the private universities to be set-up in Malaysia. UNITEN offered academic programmes which more focusing on Engineering, Information Technology, Business Management and other related programmes, which is to prepare its graduates to become knowledgeable and multi-skilled professionals.